Histopathological analysis of skin adnexal tumors: A three year study of 110 cases at a tertiary care center - Kanwalpreet Kaur; Karuna Gupta; Deepika Hemrajani; Ajay Yadav; Kalpana Mangal (Wolters Kluwer Medknow Publications, 2017)
Background: Skin adnexal tumors (SAT) encompass wide spectrum of benign and malignant tumors that differentiate toward one or more adnexal structures found in normal skin. Overall incidence of SATs is low yet they can be challenging to diagnose. Aims: The aim of this study is to study the spectrum and microscopic features of SATs. Materials and Methods: It was a retrospective cross-sectional, descriptive study conducted over a period of 3 years. Formalin fixed, paraffin-embedded sections were stained with hematoxylin and eosin for histopathological analysis. Results: Out of the total 34,400 biopsies, 110 cases were diagnosed as SATs comprising 39.09% of tumors with follicular differentiation followed by tumors showing sweat gland differentiation (37.27%), and sebaceous differentiation (23.63%). The age ranged from 5 years to 85 years and male:female ratio was 1.03:1. Most of the tumors were benign (82.73%) while only 17.27% were malignant. Pilomatricoma (28.2%) was the most common benign tumor while sebaceous carcinoma (11.8%) was the most common malignant tumor. Conclusion: Architectural features are of great importance in differentiating benign tumors from malignant.